The Study of Naphthoquinones and Their Complexes with DNA by Using Raman Spectroscopy and Surface Enhanced Raman Spectroscopy: New Insight into Interactions of DNA with Plant Secondary Metabolites - Vaverkova, Veronika (Hindawi Publishing Corporation, 2014)
Naphthoquinones represent the group of plant secondary metabolites with cytotoxic properties based on their ability to generate reactive oxygen species and interfere with the processes of cell respiration. Due to this fact, the possible cytotoxic mechanisms on cellular and subcellular levels are investigated intensively. There are many targets of cytotoxic action on the cellular level; however, DNA is a critical target of many cytotoxic compounds. Due to the cytotoxic properties of naphthoquinones, it is necessary to study the processes of naphthoquinones, DNA interactions (1,4-naphthoquinone, binapthoquinone, juglone, lawsone, plumbagin), especially by using modern analytical techniques. In our work, the Raman spectroscopy was used to determine the possible binding sites of the naphthoquinones on the DNA and to characterize the bond of naphthoquinone to DNA. Experimental data reveals the relationships between the perturbations of structure-sensitive Raman bands and the types of the naphthoquinones involved. The modification of DNA by the studied naphthoquinones leads to the nonspecific interaction, which causes the transition of B-DNA into A-DNA conformation. The change of the B-conformation of DNA for all measured DNA modified by naphthoquinones except plumbagin is obvious.